Praying and Prophesying with Coverings or Remaining Silent: A Probe into the Two Contradictory Periopae in 1 Corinthians - WANG, Nathanael Xuesheng (Journal of Research for Christianity in China (JRCC), 2022)
“veil while praying and prophesying” (1 Cor. 11:5–6) and “women should remain silent” (1 Cor. 14:34–35), it is discovered that the Apostle Paul supported gender equality and encouraged women’s participation in worship as well as other ministries. His message, “veil while praying and prophesying,” is more concerned with how the nascent church is perceived in society than it is with how women conduct themselves within the church. The conflicting pericope “women should remain silent” should be a late interpolation, as shown by both internal and external evidence, and is consistent